Slovenes in Sarajevo between 1991 and 2013 - Tomažič, Dušan; Suljić, Alija (Journal for Geography, 2020)
The article presents the basic demographic characteristics of Slovenes in Sarajevo (Bosnia and Hercegovina - BiH). A comparison of the 1991 and 2013 censuses is made. The dynamics of the number, territorial dispersion, gender, age and religious structure of Slovenes in the period before and after the war in Bosnia and Herzegovina are analyzed. The evacuation of 348 Slovenes from Sarajevo in November 1992 had a profound effect on the number, structure and territorial distribution of the Slovene population in the capital of BiH. Due to a more objective picture of Slovenes regarding their ethnicity, some other data is also included.
Keywords: Slovenes; religion; mother tongue; gender; age; Sarajevo; Bosnia and Herzegovina